EFFECT OF CHANGE IN SALINITY ON THE SURVIVAL OF PENAEUS MONODON (FABRICIUS) POSTLARVAE. - Chakraborty, R K; Bhowmik, M L; Halder, D D (Indian Journal of Fisheries, 2011)
To assess the effect'of sudden change in salinity on the postlarvae ondirect stocking or during gradual change in monsoon months, experiment wasconducted in the laboratory. Results indicated that, for a direct change in salinityin the range of 3 to 30 ppt, survival varied between 76 and 100%. During agradual change from 5 to 0.5 ppt, survival was 68% up to 2 ppt. In both thecases, survival is very poor below 2 ppt salinity